Effect of Leadership and Information System Management on Teacher Performance - Retnaningsih, Rahayu; Marsigit, M; Supriyoko, S; Nurdiyanto, Heri (International Journal of Engineering and Technology, 2018)
This study examines the influence of leadership and integrated management information system on the performance of Klaten State Senior High Schoolteachers. To create a good teacher performance is done with the utilization of information technology through integrated management information system as a means to provide services and improve teacher performance. The purpose of this research are: (1) to know the significance of leadership influence on teacher performance in Klaten State Senior High School , (2) to see the impact of the use of integrated management information system on the performance of Klaten State Senior High School teacher, (3) to know the effects of leadership and system combined management information on the performance of Klaten State Senior High School teachers. The number of samples is 95 people with data collection methods through distributing questionnaires, digging from documents and interviews. Data analysis technique in a prerequisite test of data analysis using Parson Product Moment correlation (r). Testing data normality using Chi-Square analysis with 5% significance level, and multiple regression. The results showed that leadership has a positive and significant impact on teacher performance, integrated management information system has a positive and significant effect on the performance of Klaten State Senior High School teachers, leadership and integrated management information system together also have a positive and significant impact on the performance of Klaten State Senior High School. Implications of command and integrated management information systems are vital factors that can affect the performance of Klaten State Senior High School teachers.Â